2011
DOI: 10.3171/2011.5.peds1122
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of Chiari malformation Type I following decision for conservative treatment

Abstract: Object The natural history of the Chiari malformation Type I (CM-I) is incompletely understood. The authors report on the outcome of a large group of patients with CM-I that were initially selected for nonsurgical management. Methods The authors identified 147 patients in whom CM-I was diagnosed on MR imaging, who were not offered surgery at the time of diagnosis, and in whom at least 1 year of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 44 publications
0
64
1
4
Order By: Relevance
“…Because spontaneous syrinx improvement has been reported, it is difficult to draw any conclusions from individual case reports. 5,14,16,24,29,32 Despite the theoretical basis for such a relationship, we did not find any association between elevated BMIs and risk of syrinx in our own series. On the basis of these findings and our own data, we suggest that no association between BMI and syrinx formation in patients with CM-I can be proven with the existing data.…”
Section: Discussioncontrasting
confidence: 37%
“…Because spontaneous syrinx improvement has been reported, it is difficult to draw any conclusions from individual case reports. 5,14,16,24,29,32 Despite the theoretical basis for such a relationship, we did not find any association between elevated BMIs and risk of syrinx in our own series. On the basis of these findings and our own data, we suggest that no association between BMI and syrinx formation in patients with CM-I can be proven with the existing data.…”
Section: Discussioncontrasting
confidence: 37%
“…The authors proposed that the presence of a syrinx was not always associated with symptomatic progression since only 6 of 20 patients with a syrinx had surgery during the follow-up interval, and 2 of these patients underwent surgery for reasons other than the syrinx. 31 Other investigators have added to the debate of surgery as necessary intervention in the setting of CM-I and syrinx. 8,24 Nishizawa and colleagues found over a 10-year follow-up interval that only 1 of 9 adult patients with incidental CM-I and syrinx required decompression.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the majority of patients did not progress clinically or radiologically, and no new neurological deficits were observed during a mean follow-up period of 2.83 years. 6 Another analysis by Strahle et al in 2011 found that the majority of 147 pediatric patients with CM-I, who were also managed conservatively, tended to have a benign natural history over the course of clinical and MRI follow-up, with a mean duration of 4.6 and 3.8 years, respectively.…”
mentioning
confidence: 99%
“…150,151,156 Symptoms and MRI findings are stable over time for most patients, with no symptoms or minimal symptoms that are followed without surgical treatment, although spontaneous improvement or worsening of both the CM as well as syringomyelia does occasionally occur. 150,151,156 Although most cases of clinically relevant syringomyelia are associated with CM, it may also be seen in patients with spinal cord tumor, tethered cord, or arachnoiditis. 157,158 In general, the management of syringomyelia should be directed at the primary disorder.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%